Membina pengurus pemacu ODBC pada persekitaran windows - Ibrahim, Suhaimi (Penerbit UTM Press, 1996)
ODBC is an interface specifically built to enable an aplication to communicate with one or more databases. Most of the relational databases of nowadays such as Oracle, Informix, Foxpro and others are similiar to one another in terms of concepts and internal data structures. In theory, the ODBC would examine the internal database to ensure that it conforms to the specific conditions and criterias of either as a portion or a whole system. This paper represents a part of EMAS (“enterprise management audit system”), FSKSM to describe the method of accessing data through the ODBC.